Predicative and markedness bias in loan adjectives: Dutch and Middle English - Shaw, Marlieke; De Smet, Hendrik (Neuphilologische Mitteilungen, 2022)
Previous research on loan word accommodation has shown that English‑origin verbs in Present‑day Dutch and French‑origin verbs in Late Middle English are subject to usage biases. In both language‑contact settings, loan verbs are disproportionally frequent in non‑finite and morphologically unmarked forms as compared to native verbs. The present study demonstrates that accommodation biases are also found in loan adjectives. Concretely, loan adjectives are more prevalent in predicative than in attributive syntactic position as compared to native adjectives (predicative bias), and they are more prevalent in uninflected than in inflected forms (markedness bias). The predicative bias is found to rank stronger than the markedness bias, which is consistent with the findings for verbs. Additionally, biases are more pronounced in the French‑Middle English than in the English‑Dutch contact setting. The findings indicate that direct insertion of loan-words, despite being the cross-linguistically most frequent strategy for loan word integration, is not free of obstacles, possibly due to processing costs specifically associated with loan words.